Impact of temperature and radiation on elimination of associated bacteria from preserved dried prawn, Macrobrachium lamerrei (Jahangirnagar University Journal of Biological Sciences, 2016)
The impact of different temperatures (0, 40, 60, 80 and 100° C for an hour) and radiation (0, 2.5, 5.0, 7.5 and 10.0 kGy) and combined treatment (temperature and radiation) for decontamination of bacteria from dried prawn, Macrobrachium lamarrei was also investigated under laboratory condition.The total viable bacterial (TVB), total staphylococcal (TS), total coliform (TC), total faecal coliform (TFC), total Aeromonas ( TA) and total fungal (TF) count were ranged from 2.7×108 to 5.3×108 cfu/g, 2.2×106 to 6.0×106 cfu/g, 2.9×104 to 9.5×104 cfu/g, 2.8×103 to 8.1×103 cfu/g, 5.7×103 to 8.5×103 cfu/g and 1.6×104 to 3.8×104 cfu/g respectively. Seventy eight bacterial strains were isolated and identified out of which 18 (23.07 %) were Staphylococcus aureus, 11 (14.10% ) were Micrococcus varians, 8 (10.25%) were Aeromonas hydrophila, 5 (6.41%) were Klebsiella ozaenae, 7 (8.97%) were Bacillus subtilis, 7 (8.97%) were Escherichia coli, 5 (6.41%) were Bacillus megaterium, 7 (8.97%) were Klebsiella edwardsii, 6 (7.69%) were Pseudomonas aeruginosa and 4 (5.12%) were Micrococcus radiodurans. Inactivated was more favorable at 100° C for TC, TFC, TA and TF and at 5.0 kGy for TA and TF and combined treatments (40° C+2.5 kGy, 60° C+2.5 kGy and 80° C+2.5 kGy) for TFC, TA and TF respectively. TS, TC and TVB were completely eliminated in treatment 40° C+5.0 kGy, 60° C+2.5 kGy, 80° C+2.5 kGy, 40° C+7.5 kGy, 60° C+7.5 kGy and 80° C+7.5 kGy respectively. Results demonstrated that the combination treatments were more effective than single treatment for eliminating the associated microorganisms/bacteria from dried prawn.Jahangirnagar University J. Biol. Sci. 3(1): 1-7, 2014 (June)